2022
DOI: 10.1001/jamapsychiatry.2022.0914
|View full text |Cite
|
Sign up to set email alerts
|

An Atlas of Genetic Correlations and Genetically Informed Associations Linking Psychiatric and Immune-Related Phenotypes

Abstract: IMPORTANCE Certain psychiatric and immune-related disorders are reciprocal risk factors. However, the nature of these associations is unclear.OBJECTIVE To characterize the pleiotropy between psychiatric and immune-related traits, as well as risk factors of hypothesized relevance. DESIGN, SETTING, AND PARTICIPANTSThis genetic association study was conducted from July 10, 2020, to January 15, 2022. Analyses used genome-wide association (GWA) statistics related to 14 psychiatric traits; 13 immune-related phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…Interestingly, in Mendelian randomization studies focusing on immune disorders rather than biomarkers, several psychiatric disorders where found to have a causal effect on immune disorders, rather than the other direction, including a causative effect of major depressive disorder on asthma and of schizophrenia on ulcerative colitis 245 . Nonetheless, while these findings have contributed to the growing evidence base for a possible causal association between inflammatory phenotypes and psychiatric disorders, Mendelian randomization is still based on statistical inference, and it is important to control for the extensive “horizontal” pleiotropy observed between mental traits and disorders.…”
Section: Shared Genetic Influences Between Mental Disorders and With ...mentioning
confidence: 99%
“…Interestingly, in Mendelian randomization studies focusing on immune disorders rather than biomarkers, several psychiatric disorders where found to have a causal effect on immune disorders, rather than the other direction, including a causative effect of major depressive disorder on asthma and of schizophrenia on ulcerative colitis 245 . Nonetheless, while these findings have contributed to the growing evidence base for a possible causal association between inflammatory phenotypes and psychiatric disorders, Mendelian randomization is still based on statistical inference, and it is important to control for the extensive “horizontal” pleiotropy observed between mental traits and disorders.…”
Section: Shared Genetic Influences Between Mental Disorders and With ...mentioning
confidence: 99%
“…Several studies have shown that autoimmune diseases are associated with psychiatric diseases like depression and psychosis (Jeppesen & Benros, 2019 ). In addition, genetic evidence further supports this association (Tylee et al., 2022 ).…”
Section: Tablementioning
confidence: 84%
“…The clumping procedure was conducted considering a p value of 10 −5 for the exposure GWAS. Similar to previous MR studies (2023), we used this threshold to maximize the statistical power of the analyses performed. The analysis was conducted using five MR methods: inverse variance weighted (IVW), MR-Egger, simple mode, weighted median and weighted mode (24).…”
Section: Methodsmentioning
confidence: 99%